Conformal carbon layer coating on well-dispersed Si nanoparticles on graphene oxide and the enhanced electrochemical performance - Kim, Choa; Verma, Deepak; Nam, Dong Ho; Chang, Wonyoung; Kim, Jaehoon (한국공업화학회, 2017)
Silicon nanoparticles,(SiNPs)-graphene oxide (GO) composites are synthesized using a simple, fast, and mild ball-milling route. Uniform and conformal carbon layer is coated on the surface of SiNPs and the carbon-coated SiNPs are well-dispersed on the GO matrix by forming Si-O-C linkages. A high reversible capacity of 1265 mAg(-1) at 50 mAg(-1) after 80 cycles, good rate capability of 238 mAh g(-1), at 2.5 A g(-1), and long-term cyclability of 230 mAh g(-1) at 1 A g(-1) after 800 cycles are resulted. The mild ball milling can be highly promising and scalable approach for producing high-performance Si anode material. (C) 2017 The Korean Society of Industrial and Engineering Chemistry. Published by Elsevier B.V. All rights reserved.